Strengthening school management as a strategy to improve the quality of learning in elementary schools - Izlan Sentryo; Muhamad Abas; Sarnely Uge (Jurnal Ilmiah Pendidikan Dasar, 2026)
The quality of learning greatly determines the learning process and outcomes of elementary school students, but it remains low due to ineffective school management. This study aims to analyse the practice of strengthening school management as a strategy to improve the quality of learning, analyse teachers' perceptions and analyse the effectiveness of strengthening school management. The method used is a mixed method. The design is an exploratory sequential design. Data collection was carried out using interview guidelines and questionnaires. The technique of data analysis was carried out using interactive qualitative and descriptive quantitative. The result of this study showed that: (1) there are eight practices for strengthening school management as a strategy to improve the quality of learning, namely strengthening school's vision and mission, strengthening leadership, strengthening the curriculum, strengthening students, strengthening teaching staff, strengthening finance, strengthening infrastructure, strengthening administration and strengthening public relations; (2) teachers' perceptions of strengthening school management are average in good category, it means that teachers have good perceptions of strategies for strengthening school management; (3) strengthening school management has a positive correlation by improving quality of learning. Evidenced by the Pearson product-moment correlation coefficient (r) = 0.775, it means that close relationship between variables included in the strong or high category and has a positive and significant influence on improving the quality of learning. The more effective the strengthening of school management, the better the quality of learning. In conclusion, the implemented practice of strengthening school management is considered effective as a strategy to improve the quality of learning at Elementary School.